ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN SIGI PERIODE 2012-2016 - sari, Jeni ninsi (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to measure performance using indicators achievement between targets and realization of programs based on RAPBD. With measurement of financial performance, it is expected that will provide overview the condition of Regional Financial Performance in DPPKAD SIGI. This research uses quantitative descriptive method, which is aim get detailed picture about regional financial of SIGI. The results of study, (1) Fiscal Decentralization Degree Ratio can be categorized as Very Less, from 2012 to 2016 the value of average expenditure below 10%2.00%; 2.07%; 3.10%; 2.37%; and 2.70%. (2) ratio of Regional Financial Independence is very low and the pattern of relationships including Instructive relationship patterns, from 2012 to 2016 the value of each ratio is: 2.05%; 2.12%; 3.22%; 2.80%; and 2.70%. (3) Regional Financial Efficiency Ratios from 2012 to 2016 the percentage value fluctuates. (4) PAD Effectiveness Ratio is known that effectiveness of local government finances from 2012 has been effective that is equal to 101.20%. While 2013 until 2016 Not Effective because its effectiveness still below 100%. (5) Harmony Ratios of Local Governments most of funds with average expenditure above 70% so that capital expenditure is relatively small with average below 60%.